A General Strategy for the Synthesis of Enantiomerically Pure Azetidines and Aziridines through Nickel‐Catalyzed Cross‐Coupling. Issue 20 (27th March 2015) - Jensen, Kim L.; Nielsen, Dennis U.; Jamison, Timothy F.
Abstract In this communication, we report a straightforward synthesis of enantiomerically pure 2‐alkyl azetidines. The protocol is based on a highly regioselective nickel‐catalyzed cross‐coupling of aliphatic organozinc reagents with an aziridine that features a tethered thiophenyl group. Activation by methylation transforms the sulfide into an excellent leaving group and triggers the formation of the 2‐substituted azetidine core structure by cyclization. In addition, we have expanded this concept to the synthesis of enantiomerically pure, terminal alkyl aziridines. Coupling of a TMS‐protected aziridine alcohol, followed by acidic work‐up to remove the silyl group, provides 1, 2‐amino alcohol products that are readily cyclized to aziridines. Both of these sequences display excellent functional group tolerance and deliver the desired azetidine and aziridine products in good to excellent yields.